Interactions of PIN and PGP auxin transport mechanisms. (22nd January 2007) - Bandyopadhyay, A.; Blakeslee, J.J.; Lee, O.R.; Mravec, J.; Sauer, M.; Titapiwatanakun, B.; Makam, S.N.; Bouchard, R.; Geisler, M.; Martinoia, E.; Friml, J.; Peer, W.A.; et al.
Abstract : Polarized transport of the plant hormone auxin influences multiple growth processes in plants and is regulated by plasma-membrane-localized efflux and uptake carriers. The PGP (P-glycoprotein) ABC transporters (ATP-binding-cassette transporters), PIN (pin-formed) subfamily of major facilitator proteins and members of AUX/LAX families have been shown to independently transport auxin both in planta and in heterologous systems. However, PIN- and PGP-mediated transport in heterologous systems exhibits decreased substrate specificity and inhibitor-sensitivity compared with what is seen in plants and plant cells. To determine whether PIN–PGP interactions enhance transport specificity, we analysed interactions of the representative auxin-transporting PGPs with PIN1 and AUX1 in planta and in heterologous systems. Here, we provide evidence that PINs and PGPs interact and function both independently and co-ordinately to control polar auxin transport and impart transport specificity and directionality. These interactions take place in protein complexes stabilized by PGPs in detergent-resistant microdomains.